Analisis Penalaran Proporsional Siswa dengan Gaya Belajar Auditori dalam Menyelesaikan Soal Perbandingan - Aan Putra; Yetiona Tensa; Selvia Erita (Departement of Mathematics Education, 2020)
Comparison, ratio, and proportion were any problems encountered in everyday life. To understand it, high-level proportional reasoning is needed. The analysis for this ability was important, especially on any students with an auditory learning style that rely on hearing to understand the lesson. This study attempts to describe the proportional reasoning level of students with the auditory learning style in solving the proportion problems. Research informants were selected using purposive sampling technique. Based on the results of the learning style questionnaire, the researcher obtains 5 students with an auditory learning style. The research informant was given some question about the proportion, then were they interviewed about the strategies used in solving the problems. The results of the analysis of student answers and interviews indicate that 4 in 5 students have proportional reasoning at the qualitative level. Only 1 in 5 students reach the multiplicative level. Perbandingan, rasio dan proporsi merupakan permasalahan yang sering ditemui dalam kehidipan sehari-hari. Untuk memahaminya diperlukan kemampuan penalaran proporsional. Analisis kemampuan ini menjadi penting terutama bagi siswa dengan gaya belajar auditori yang mengandalkan pendengaran untuk memahami materi. Penelitian ini bertujuan untuk mendiskripsikan tingkat kemampuan penalaran proporsional siswa dengan gaya belajar auditori dalam menyelesaikan soal perbandingan. Informan penelitian dipilih menggunakan teknik purposive sampling. Berdasarkan hasil angket gaya belajar, ditemukan 5 siswa yang memiliki gaya belajar auditori. Setelah menyelesaikan soal perbandingan, informan penelitian diwawancarai mengenai strategi penyelesaian soal. Hasil penelitian menunjukkan bahwa 4 dari 5 siswa memiliki kemampuan penalaran proporsional level kualitatif dan hanya satu siswa yang mencapai level multiplikatif.